Digital World Threat Preparedness For Digital Transformation Acceleration Policy In Indonesia - Dwi Jati Marta; IDK Kertra Widana; Adi Subiyanto; Pujo Widodo; Kusuma, Kusuma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Digital transformation is a must for Indonesia in facing global dynamics in this digital era. Through the digital transformation acceleration policy, Indonesia seeks to accelerate economic growth, improve the quality of public services, and strengthen national resilience in the digital era. The purpose of this paper underlines the importance of Indonesia's preparedness in facing the threats of the digital world, both in terms of cybersecurity, data privacy violations and other negative impacts. The method used is a qualitative research method with data reviewed through literature studies. The results show that the importance of this preparedness covers various aspects, ranging from cybersecurity infrastructure to community digital literacy to overcome challenges and risks in building a strong digital defense. In addition, there is a need for concrete steps to overcome obstacles and challenges in implementing digital transformation acceleration policies. This includes strengthening technological infrastructure, improving digital literacy, encouraging the involvement of all stakeholders, and ensuring supportive regulations and adequate privacy protection. Throughout the analysis, it is important to understand that digital transformation is not an end goal, but an ongoing journey. By identifying and addressing the challenges and risks that arise, Indonesia can optimally utilize the potential of digital transformation to achieve sustainable development and protect people's security and privacy in this digital era.